Crime and punishment - Dostoyevsky, Fyodor (London : Arcturus, 2018)
A mesmerizing detective story with an intriguing and multifarious central character, Crime and Punishment hinges on the ethical dilemmas and angst of the student Rodion Romanovich Raskolnikov who plans and implements the murder of a ruthless pawnbroker. Rodion convinces himself that in killing her he will both solves his financial problems and divests the world of a wicked leech. But can he commit a murder and escape all consequences?
Keywords: Novel -- Fiction -- Russian literature